Neutrophil extracellular traps and macrophage activation contibute to thrombosis and post-covid syndrome in SARS-CoV-2 infection - Serrano-Gonzalo, Irene; Menéndez-Jandula, Bárbara; Franco-García, Esther; Arévalo-Vargas, Isidro; Lahoz-Gil, Calos; Latre, Paz; Roca-Esteve, Sonia; Köhler, Ralf; López de Frutos, Laura; Giraldo, Pilar (Frontiers in Immunology, 2025)
BackgroundSARS-CoV-2 infection activates macrophages and induces the release of neutrophil extracellular traps (NETs). Excess NETs is linked to inflammatory and thrombotic complications observed in COVID-19.AimTo explore the impact of NETs and macrophage activation on SARS-CoV-2-infected patients who developed complications.MethodsWe included 30 patients from the first (March 2020) and 30 from the second wave (July 2021), collecting two plasma samples at diagnosis and seven days later. Data on demographics, comorbidities, and basic analytical data were compiled. NETs markers (myeloperoxidase (MPO), neutrophil elastase (NE), p-selectin (P-SEL) and S100A8/S100A9 heterodimer (MRP)) and macrophage activation markers (Chitotriosidase activity (ChT), CCL18/PARC and YKL-40) were measured.ResultsThe first wave had higher incidences of post-COVID syndrome, ICU admissions, and mortality. Patients of each wave showed elevated blood cells, liver enzymes, and coagulation markers at the time of diagnosis, with fibrinogen and D-Dimer differing between waves. NET and macrophage markers, NE, MPO, MRP, DNAse, ChT, and CCL18 were elevated, while P-SEL, cfDNA, and YKL-40 were decreased if compared to controls. A decrease in NE and DNAse is a link to lower levels of these two markers in complications versus without complications.ConclusionsThis study emonstrates alterations in NETs and macrophage activation markers in COVID-19 patients, indicating an imbalance in inflammatory response regulation.